Peer Guidance: development of Children's Wellbeing on Addicted Parents - Supriyanto, Agus; Hendiani, Nurlita; Wahyudi, Amien; Purwadi, Purwadi; Fauziah, Mufied (Counsellia: Jurnal Bimbingan dan Konseling, 2020)
Children are victims of parents who are undergoing drug rehabilitation programs. The factor is that parents do not accompany the education process for a specified period. Peer approaches by school counselors play a significant role in developing children's welfare in school. The goals of this study were to determine the application of peer guidelines for the development of healthy children of addicted parents. This research uses a literature study and a case study method. The data used in the study originated from the literature, as well as the primary references and interviews. Interviews conducted to parents of drug users in the large centers of drug rehabilitation. The analysis used in the descriptive study of literature method and case study method study. The findings conclude that the welfare of children from drug abuser's parents causes stress in children to influence the psychological, social, and academic dimensions. Peer guidance applications provide support for the education of children from parents who are undergoing drug rehabilitation programs and success in school. Peer skills implement openness, asking questions, and reflection, and empathy. The impact is child welfare in the psychological, social, and academic dimensions. Collaboration between addicted counselors, school counselors, parents, and guardians is needed